The Representation of Batak Toba Family Values in the Mangongkal Holi Tradition: A John Fiske Semiotic Analysis of Tulang Belulang Tulang - Nacha Wahyu Micha Sitompul; Augustin Mustika Chairil (International Journal of Social, Economic, and Business, 2026)
Mangongkal Holi is traditional ceremony to pay final respects to deceased ancestors by transferring their bones and reuniting them in a family monument or batu na pir. The Batak Toba greatly respects and protects their families, which play a very important role in traditional customs and social life. Dalihan Na Tolu forms the basis for regulating social roles, traditional positions, kinship, and conflict resuolution within Batak Toba families. The three main pillars of dalihan na tolu are hula-hula, boru and dongan tubu. The film Tulang Belulang Tulang is a cultural product that presents the reality of the Batak Toba persistence in maintaining Batak Toba customs to improve the social class (prestige) of their families oreder to obtain hasangapon, hamoraon, and hagabeon, as well as the challeges gaced by Batak Toba families in rturning from their travel to their hometwons in Batak land (Bona Pasogit). Therefore, this study conducted t analyze in depth how the values of the Batak Toba family are represented throught the Mangongkal Holi traditional in the film Tulang Belulang Tulang using qualitative research methods with a constructivist paradigm. Twenty-two shots were analyzed using John Fiske’s three-level analyziz technique of  “Television Code” nmley the level of reality, the level of representation and the level of ideology. The result of this study found that Batak Toba families highly values social and family honor in the eyes og their community. The rise in social class or prestige of Batak Toba families is reflected in the activities and customs carried out by the family. The film Tulang Belulang Tulang actualizes the reality of Batak Toba families in the Batak Toba cultural community, which still biews families through their social class and status, as reflected in the actualization of Batak Toba traditional celebrations. The realization of the philosophy of hamoraon, hagabeon and hasangapon is a benchmark for assessing the success and prosperity of Batak Toba families, which will be considered successful and respected (having authority) in practicing “namar adat”.